2016
DOI: 10.1093/nar/gkw1109
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of nonsense mediated decay by rapamycin

Abstract: Rapamycin is a naturally occurring macrolide whose target is at the core of nutrient and stress regulation in a wide range of species. Despite well-established roles as an inhibitor of cap-dependent mRNA translation, relatively little is known about its effects on other modes of RNA processing. Here, we characterize the landscape of rapamycin-induced post-transcriptional gene regulation. Transcriptome analysis of rapamycin-treated cells reveals genome-wide changes in alternative mRNA splicing and pronounced ch… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 56 publications
(89 reference statements)
4
22
0
Order By: Relevance
“…Our analysis of intron retention suggested that coupling of AS-NMD is modulated under DR, in part, by changing the selectivity toward which transcripts are detected and degraded. Observations are in line with those obtained from cell culture exposed to rapamycin, a drug that inhibits the DR-related TOR pathway, in which the selectivity of NMD toward transcripts was also modulated (Martinez-Nunez et al, 2016). Taken together, studies point to an adaptive mechanism of DR that functions by controlling productive splicing and turnover.…”
Section: Discussionsupporting
confidence: 85%
“…Our analysis of intron retention suggested that coupling of AS-NMD is modulated under DR, in part, by changing the selectivity toward which transcripts are detected and degraded. Observations are in line with those obtained from cell culture exposed to rapamycin, a drug that inhibits the DR-related TOR pathway, in which the selectivity of NMD toward transcripts was also modulated (Martinez-Nunez et al, 2016). Taken together, studies point to an adaptive mechanism of DR that functions by controlling productive splicing and turnover.…”
Section: Discussionsupporting
confidence: 85%
“…Our analysis of intron retention suggested that coupling of AS-NMD is modulated under DR, in part, by changing the selectivity towards which transcripts are detected and degraded. Observations are in line with those obtained from cell culture exposed to rapamycin, a drug that inhibits the DR-related TOR pathway, in which the selectivity of NMD towards transcripts was also modulated (Martinez-Nunez et al, 2016). Taken together, studies point to an adaptive mechanism of DR that functions by controlling productive splicing and turnover.…”
Section: Dr Increases As Products and Differentially Regulates Nmd Tasupporting
confidence: 82%
“…For almost 50 years, polysome profiling has provided a gold-standard method to precisely assay functional genome readout at a given time point [5]. Indeed, it has for many years been widely applied to assess translational fitness under various physiological conditions relating to cellular stress [6][7][8][9], as well as being applied to study ribosome biogenesis and the functional roles of proteins involved in translation, regulation of mRNA stability and miRNA-mediated silencing [10][11][12][13]. Although, originally established in yeast, polysome profiling has been successfully introduced in mammalian cell, plant, bacteria and translation competent cell-free model systems [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%